Critical Thinking as an Integral Outcome in Translator and Interpreter Training - Kuleli, Mesut; Tuna, Didem (English Studies at NBU, 2022)
The aim of this study is to investigate the critical thinking attitudes of translator and interpreter candidates with a view to coming up with recommendations on curriculum development in Translation and Interpretation undergraduate studies. A "Critical Thinking Skills Scale" was administered to 354 translation and interpretation students from five universities in Turkey. Independent sample t-test, one-way ANOVA and post-hoc Scheffe test were used in data analysis. With the highest and lowest attitudes found for receptiveness and inquiry skills respectively, the total critical thinking attitudes of translator candidates are above the average. The class level of the students is inversely correlated with total scores for critical thinking attitudes, in addition to the flexibility and judiciousness subdimensions. Moreover, translator candidates of the Bulgarian language have the highest total scores for critical thinking attitudes as compared to those of English, French, Persian and German. The results show that innovative curricula involving related tasks and activities must be developed for translation and interpretation departments to enhance translator candidates' critical thinking skills, bearing in mind the very nature of the act of translation and interpretation.